Lo sviluppo delle nanoscienze e la didattica universitaria di base - A. Floriano, Michele; Venanzi, Mariano (Chimica nella Scuola, 2022)
Summaries of the two specific sessions of the XIII edition of the School of Education Research and Chemistry Didactics “Ulderico Segre”, organized by DD-SCI, on Nanoscience and on how this discipline may affect the teaching of chemistry undergraduate courses are reported. Modern microscopy techniques, which allow to obtain images with atomic resolution, were described and the interpretation of these images was discussed. Furthermore, the size dependence of physical and chemical properties of matter at the nanometric scale was analysed. The possibility of obtaining supramolecular structures with specific properties by self-assembly was also highlighted.